Українська політична лінгвістика в Україні: фундаментальні і прикладні проблеми - Кондратенко, Н.В. (Мовознавство, 2016)
У статті розглянуто етапи становлення і сучасний стан політичної лінгвістики як галузі фундаментального і прикладного мовознавства в Україні. Окреслено основні періоди розвитку політичної лінгвістики в зарубіжному мовознавстві та загалом в гуманітарній науці, що зумовило її міждисциплінарний характер. Представлено проблеми фундаментального характеру та шляхи їх розв’язання в українській політичній лінгвістиці. The article deals with the stages of formation and present state of political linguistics as a field of fundamental and applied linguistics in Ukraine. The basic period of political linguistics in general and in the humanities, led to its interdisciplinary nature. The necessity of the scientific study of political linguistics as a modem linguistic science industry in Ukraine. The author determined new approaches to the analysis of political discourse — cognitive linguistic, lingual pragmatic and suggestive linguistic. Within each approach generalized concept of leading Ukrainian scientists and research perspectives are presented. Applied linguistics political aspects are identified as a priority at the current stage of scientific development.